Comparative studies on glycerol monooleate- and phytantriol-based cubosomes containing oridonin in vitro and in vivo. (3rd April 2017) - Shi, Xuan; Peng, Tingting; Huang, Ying; Mei, Liling; Gu, Yukun; Huang, Jiayuan; Han, Ke; Li, Ge; Hu, Chunli; Pan, Xin; Wu, Chuanbin
Abstract: To improve the solubility and bioavailability of oridonin (ORI), glycerol monooleate lipid (GMO)- or phytantriol (PYT)–Poloxamer 407–propylene glycol–water systems were firstly used to develop cubosomes containing ORI for oral delivery. These cubosomes prepared through the fragmentation of bulk gels under homogenization conditions of 1200 bar and nine cycles had a mean particle size of around 200 nm with narrow size distribution, and ORI encapsulation efficiency over 85%. Powder X-ray diffraction and differential scanning calorimetry indicated that ORI was in an amorphous or molecular form in the cubosomes. The internal structures of GMO- and PYT-based cubosomes were revealed by small-angle X-ray scattering as a bi-continuous cubic liquid crystalline phase with Im3m and Pn3m geometry, respectively. About 80% of ORI was released in vitro from GMO- and PYT-based cubosomes at 24 h, showing a sustained release kinetics fitted with Higuchi's equation. The pharmacokinetic study in rats showed that the PYT-based cubosomes significantly enhanced the adsorption of ORI as compared to the GMO-based cubosomes and ORI suspension, with evidence of longer half-life and greater relative bioavailability ( p  < 0.01). Therefore, the PYT-based cubosomes containing ORI might be proposed as a promising candidate carrier for the efficient delivery of drug with therapeutic treatment.